Tourist Behavior is Changing as a Result of The Mini Vlog Trend - Siwiningtyas, Margareta Lingga; Prihatno; Hermawan, Hary (Media Wisata, 2023)
Social media platforms like Tiktok and Instagram have been shown to affect how contemporary tourists act. Since the mini vlog trend began, creating tiny vlogs has spread to the world of tourism, particularly in tourist destinations, for their personal needs and employment. It has become a must for those who experience the slight vlog trend. This study aims to analyse the pattern of changes in tourist behaviour in tourist hotspots brought on by the micro vlog trend. This paper employs a phenomenological approach and a qualitative research methodology. The main focus of the study is the experience of research participants who have accounts and actively use the social media platforms Tiktok and Instagram during the two stages, namely before and after the mini vlog craze. The mini-vlog trend in tourist places impacts each subject's psychological dynamics and behavioural patterns in two different phases, namely the phase before and after the mini-vlog trend, according to the research findings on four subjects presented in this article. Changes can be seen in travel locations, prepared travel gear, and activities when visiting tourist destinations. This article aims to enlighten readers about mini-vlog trends that influence tourist behaviour and how mini-vlog trends might enhance the tourism industry by serving as a promotional tool for tourist locations.